A dual composite resin injection molding technique with 3D-printed flexible indices for biomimetic replacement of a missing mandibular lateral incisor - Watanabe, Keiichiro; Tanaka, Eiji; Kamoi, Kohei; Tichy, Antonin; Shiba, Takahiko; Yonerakura, Kazuhide; Nakajima, Masatoshi; Han, Ruonan; Hosaka, Keiichi (Journal of prosthodontic research, 2024)
PATIENTS: This case report presents a minimally invasive approach to replace a missing mandibular lateral incisor using a dual-injection molding technique with flowable composite resins. Integrated with a comprehensive digital workflow, this method achieves a structurally and esthetically biomimetic, bi-layered prosthetic solution. A 34-year-old woman with congenital absence of a mandibular lateral incisor was successfully rehabilitated using a direct composite resin-bonded fixed partial denture (RBFPD). DISCUSSION: Two specialized three-dimensional (3D)-printed flexible indices stabilized by a custom-designed 3D-printed rigid holder were employed to ensure the meticulous injection molding of flowable composite resins formulated to emulate the inherent chromatic gradations between dentin and enamel. The inherent flexibility of the indices, combined with the holder, facilitated accurate and seamless adaptation to the complex morphological features of the dental arch, thereby mitigating the challenges commonly associated with rigid 3D-printed resin indices. CONCLUSIONS: The bilayered direct composite RBFPD using 3D printed flexible indices prepared with a full digital workflow has several advantages over other dental prosthetic solutions, including noninvasiveness, cost-effectiveness, biomimetic esthetics, repairability, and shortened treatment times. Although the initial results are promising, further longitudinal studies with larger patient cohorts are required to confirm the long-term efficacy of this approach.
Keywords: dospělí; složené pryskyřice; Humans; Biomimetics; Injection molding technique; 3D tisk; Mandible; mandibula; řezáky; Composite Resins; Adult; Direct composite resin-bonded fixed partial denture; zubní náhrady částečné pevné lepené pryskyřicí; anodoncie; ženské pohlaví; Printing, Three-Dimensional; Digital workflow; Anodontia; Missing lateral incisor; lidé; biomimetika; Denture, Partial, Fixed, Resin-Bonded; Incisor; Bi-layered restoration; Female